2013
DOI: 10.1080/10503307.2013.807379
|View full text |Cite
|
Sign up to set email alerts
|

Whatelseare psychotherapy trainees learning? A qualitative model of students' personal experiences based on two populations

Abstract: After an introductory course in experiential-integrative psychotherapy, 21 graduate students provided personal narratives of their experiences, which were analyzed using the grounded theory method. Results produced 37 hierarchically organized experiences, revealing that students perceived multiple changes in both professional (i.e., skill acquisition and learning related to the therapeutic process) and personal (i.e., self growth in a more private sphere) domains. Analysis also highlighted key areas of difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 23 publications
2
29
1
Order By: Relevance
“…Our findings generally support the observation that counselors tend to develop their personal working styles even at the beginning of their careers (Auxier et al, 2003;Carlsson et al, 2011;Pascual-Leone et al, 2013). As a result of the analysis, we conceptualized Personal Core and Professional Extension as two components of a personal working style and we elaborated two broad types of interaction between these two components which represent the directions "from inside out" (i.e.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our findings generally support the observation that counselors tend to develop their personal working styles even at the beginning of their careers (Auxier et al, 2003;Carlsson et al, 2011;Pascual-Leone et al, 2013). As a result of the analysis, we conceptualized Personal Core and Professional Extension as two components of a personal working style and we elaborated two broad types of interaction between these two components which represent the directions "from inside out" (i.e.…”
Section: Discussionsupporting
confidence: 81%
“…Stoltenberg, 1981). Several studies, however, suggest that even trainees at the beginning of their career can base their selections and development on personal characteristics and preferences (Auxier, Hughes, & Kline, 2003;Carlsson et al, 2011;Pascual-Leone, Rodriguez-Rubio, & Metler, 2013).…”
mentioning
confidence: 95%
“…Even so, more recent reviews of the training outcome literature (Hill & Lent, 2006) found gains to be uniform across these groups. Interestingly, however, more qualitative research comparisons suggest there are indeed unique gains for undergraduate as compared to graduate students (Pascual-Leone, Rubio-Rodriguez, & Metler, 2013;Pascual-Leone, Wolfe, & O'Connor, 2012).…”
Section: Findings On Psychotherapy Trainingmentioning
confidence: 95%
“…Grounded theory analysis (GTA; Glaser & Strauss, ; Glaser, ; Strauss & Corbin, ; see also Dourdouma & Moertl, ) is a flexible approach that allows the researcher to generate a theory of the phenomenon under investigation through the exploratory examination of the informants. GTA is ‘an inductive interpretive process used to explore subjective experiences for the purposes of theory generation’ (Pascual‐Leone, Rodriguez‐Rubio, & Metler, , p. 582). GTA has been applied to a wide range of themes by qualitative researchers and is a method adopted by other health and social science disciplines, including counselling and psychotherapy (Fassinger, ; Levitt, Butler, & Hill, ; Pascual‐Leone et al, ; Ponteronto, ; Rober, Elliott, Buysse, Loots, & Corte, ).…”
Section: Methodsmentioning
confidence: 99%